Sustainable workforce: South African Audiologists and Speech Therapists - Pillay, Mershen (Hum Resour Health, 2020)
BACKGROUND: Audiologists and Speech Therapists play a vital role in addressing sustainable development goals by supporting people who are marginalised due to communication challenges. The global burden of disease and poor social living conditions impact negatively on the development of healthy communication, therefore requiring the services of Audiologist and Speech therapists. Against this background, we examined the demographic profile and the supply, need and shortfall of Audiologists and Speech Therapists in South Africa. METHODS: The data set was drawn from the Health Professions Council of South Africa (HPCSA) registers (for 2002–2017) for the speech, language and hearing professions. This demographic profile of the professions was created based on the category of health personnel; category of practice, geographical location, population group (race) and sex. The annual supply was estimated from the HPCSA database while the service–target approach was used to estimate need. Additional need based on National Health Insurance Bill was also included. Supply–need gaps were forecast according to three scenarios, which varied according to the future intensity of policy intervention to increase occupancy of training places: ‘best guess’ (no intervention), ‘optimistic’ (feasible intervention), and ‘aspirational’ (significant intervention) scenarios up to 2030. RESULTS: Most (i.e. 1548, 47.4%) of the professionals are registered as Audiologists and Speech Therapists, followed by 33.5% registered as Speech Therapists and 19.1% registered as Audiologists. Around 88.5% professionals registered as Audiologists and Speech Therapists are practising independently, and 42.6% are practising in the Gauteng province. The profession is comprised majorly of women (94.6%), and in terms of the population groups (race), they are mainly classified as white (59.7%). In 2017, in best guess scenario, there is a supply–need gap of around 2800 professionals. In the absence of any intervention to increase supply capacity, this shortfall will remain same by the year 2030. By contrast, in aspirational scenario, i.e. supply is increased by 300%, the forecasted shortfall for 2030 reduces to 2300 from 2800 professionals. CONCLUSIONS: It is clear that without significant interventions, South Africa is likely to have a critical shortfall of Audiologists and Speech Therapists in 2030. Policy-makers will have to carefully examine issues surrounding the current framework regulating training of these and associated professionals, in order to respond adequately to future requirements.